Radio Identification Methods for Archaeological Human Teeth Remains: A Scoping Review - Fahmi Oscandar; Dia Adinda Surya; Lutfi Yondri (KALPATARU, 2022)
Identification of archaeological human teeth findings using a non-destructive method such as a radiograph is limited. Various methods have been used for archaeological human teeth findings, including 2D and 3D radiographs. This study examines the extent to which it is used, its advantages, and its limitations using the scoping review method. The search for articles referred to the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA-ScR) was conducted through PubMed, Scopus, and ScienceDirect, published from 2012-2022. Articles were screened and assessed for eligibility. The initial search found 249 articles. After evaluating the eligibility criteria, 15 articles were selected. Studies addressing the criteria and other aspects were identified. Based on a study conducted on articles that met the criteria, it was concluded that the radio identification method has been utilized for various identification and that the most frequently used radio identification method is cone-beam computed tomography (CBCT).